Analisis Ketimpangan dan Implikasi Sosial-Ekonomi Pekerja Media: Studi Kasus Podcast Deddy Corbuzier - Ruslita, Gita; Widaningsih, Titi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The development of the digital media industry has changed the work landscape for media workers, including in the podcast ecosystem. Deddy Corbuzier's podcast as one of the largest podcasts in Indonesia represents this change, where individuals can become independent producers with great influence. However, digital capitalism creates flexible working conditions but is also vulnerable to exploitation, including wage inequality, high work flexibility, and lack of labor protection. Additionally, controversies in podcast content are often used as a capitalization strategy to increase exposure and profits. This research aims to analyze political economic inequality in the digital media industry through a case study of Deddy Corbuzier's Podcast. Using qualitative methods and communication political economy approaches based on Karl Marx's critical theory, this study examines how digital capitalism shapes the working conditions of media workers and the resulting socio-economic impacts. Data was obtained through case studies, literature reviews, and analysis of YouTube content. The results show that although the digitalization of media opens up new opportunities, the benefits remain concentrated on channel and platform owners, while media workers face job uncertainty. Therefore, fairer regulations are needed to protect media workers and minimize exploitation in the digital economy.